Unraveling Cerebral Stenosis: Current Insights Into Diagnosis and Neurointervention Management - Kholida, Baiq Hilya; Wiracakra, I Gusti Lanang Krisna; Gea, Endah Irnanda Ulfah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Intracranial atherosclerotic stenosis (ICAS) represents a major cause of ischemic stroke worldwide, particularly among Asian, African, and Hispanic populations. Atherosclerosis is the primary underlying pathology, and severe symptomatic stenosis (70–99%) is associated with up to a 25% risk of recurrent stroke within two years. Accurate diagnosis and optimal management are critical to improving outcomes and preventing recurrence. A comprehensive literature review was conducted using Google Scholar, PubMed, and ScienceDirect databases for studies published between 2012 and 2025. Relevant articles addressing the etiology, pathophysiology, diagnostic imaging, and therapeutic approaches to ICAS were analyzed and synthesized. ICAS is strongly associated with modifiable risk factors; hypertension, diabetes mellitus, dyslipidemia, and smoking as well as non-modifiable factors such as age, sex, and ethnicity. Diagnostic confirmation relies on neuroimaging modalities including CTA, MRA, and digital subtraction angiography (DSA), with DSA remaining the gold standard. Aggressive best medical therapy (BMT), consisting of dual antiplatelet therapy, statins, risk-factor control, and lifestyle modification, significantly reduces stroke recurrence. Endovascular revascularization and surgical procedures such as encephaloduroarteriosynangiosis (EDAS) may be considered for selected high-grade or refractory cases. ICAS remains a leading cause of recurrent ischemic stroke. Early detection through advanced imaging and comprehensive, individualized managementprimarily with medical therapy, supplemented by endovascular or surgical intervention when indicated offers the best outcomes for affected patients.